The Continuing Relevance of John Dewey : Reflections on Aesthetics, Morality, Science, and Society. - Hickman, Larry A. (Value Inquiry Book Series, 2010)
The present volume encapsulates the contemporary scholarship on John Dewey and shows the place of Dewey's thought on the philosophical arena. The authors are among the leading specialists in the philosophy of John Dewey from universities across the US and in Europe.